Feasibility Study on a Segmented Ferrofluid Flow Linear Generator for Increasing the Time-Varying Magnetic Flux - Lee, Won-Ho; Lee, Se-Hee; Lee, Sangyoup; Lee, Jong-Chul (AMER SCIENTIFIC PUBLISHERS, 2018)
Nanoparticles and nanofluids have been implemented in energy harvesting devices, and energy harvesting based on magnetic nanofluid flow was recently achieved by using a layer-built magnet and micro-bubble injection to induce a voltage on the order of 10-1 mV. However, this is not yet suitable for some commercial purpose. In order to further increase the amount of electric voltage and current from this energy harvesting the air bubbles must be segmented in the base fluid, and the magnetic flux of the segmented flow should be materially altered over time. The focus of this research is on the development of a segmented ferrofluid flow linear generator that would scavenge electrical power from waste heat. Experiments were conducted to obtain the induced voltage, which was generated by moving a ferrofluid-filled capsule inside a multi-turn coil. Computations were then performed to explain the fundamental physical basis of the motion of the segmented flow of the ferrofluids and the air-layers.